2017
DOI: 10.3389/fnins.2017.00665
|View full text |Cite
|
Sign up to set email alerts
|

Neural Interfaces for Intracortical Recording: Requirements, Fabrication Methods, and Characteristics

Abstract: Implantable neural interfaces for central nervous system research have been designed with wire, polymer, or micromachining technologies over the past 70 years. Research on biocompatible materials, ideal probe shapes, and insertion methods has resulted in building more and more capable neural interfaces. Although the trend is promising, the long-term reliability of such devices has not yet met the required criteria for chronic human application. The performance of neural interfaces in chronic settings often deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
141
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(141 citation statements)
references
References 239 publications
(339 reference statements)
0
141
0
Order By: Relevance
“…Previously, there have been studies examining and comparing a variety of existing array configurations; however, a comprehensive systematic evaluation of the geometric features has not been performed on currently relevant devices. Some of the most studied array geometries include the Utah array (Figure B) and the Michigan array (Figure C), as they offer advantages over more traditional microwire electrode designs, such as noise reduction, increased ease of recording site definition, and reduction in the number of microdrives required to implant the electrode into the brain . Utah arrays are characterized by grids of silicon microelectrodes, each of which are ≈1 mm in length, with intermediate spacings of 0.4 mm and a surface area of about 12.96 mm 2 .…”
Section: Microelectrode Array Modifications For Improving the Neuralmentioning
confidence: 99%
“…Previously, there have been studies examining and comparing a variety of existing array configurations; however, a comprehensive systematic evaluation of the geometric features has not been performed on currently relevant devices. Some of the most studied array geometries include the Utah array (Figure B) and the Michigan array (Figure C), as they offer advantages over more traditional microwire electrode designs, such as noise reduction, increased ease of recording site definition, and reduction in the number of microdrives required to implant the electrode into the brain . Utah arrays are characterized by grids of silicon microelectrodes, each of which are ≈1 mm in length, with intermediate spacings of 0.4 mm and a surface area of about 12.96 mm 2 .…”
Section: Microelectrode Array Modifications For Improving the Neuralmentioning
confidence: 99%
“…a) Scheme of cortex section. Reproduced under the terms of Creative Commons license . Copyright 2017, the Authors.…”
Section: Implantable Neuroprostheses In Clinical Applicationsmentioning
confidence: 99%
“…As a particularly useful method for spatially resolved measurements in challenging biological systems, such as intracortical recordings, this technology is still developing [141]. It has been shown that flexible neural probes can be inserted into living tissue, with the assistance of a stiffener assembly, in a further example of an application of electrochemical imaging in a location inaccessible to standard SEPM methods operated with a mobile scanning probe [142].…”
Section: Microelectrode Arrays and Large-scale Integration Chipsmentioning
confidence: 99%